KAJIAN KESIAPAN KEAMANAN INFORMASI INSTANSI PEMERINTAH DALAM PENERAPAN E-GOVERNMENT - Setiawan, Ahmad Budi (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2013)
This study aims to observe the readiness of Implementation Information Security Governance either in government agencies or regional ministerial level for the implementation of e-government. The analysis in this study was done by mapping the information security aspects of Indonesian e-Government Ranking index (index PeGI). The results of this study had concluded that using a framework of information security aspects index that is mapped to the Indonesian e-Govenment Ranking index is helpful to see the readiness of government information security.